Effects of NPK Fertilizer and Arbuscular Mycorrhizal Fungi (AMF) on the Growth of Oil Palm (Elaeis guineensis Jacq.) Seedlings - Sahru Ananda Ramadhan; Listyawati Indra Putri; Praditya Rizqi Novanto; Fatimah Nur Istiqomah; Aidil Azhar (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Nutrients in the nursery stage significantly impact the cultivation of oil palm seedlings. The study aimed to investigate the effects of NPK fertilizer and Arbuscular Mycorrhizal Fungi (AMF) on the growth of oil palm seedlings. A Randomized Complete Block Design with a single factor was employed, consisting of six treatment levels and four replications. The treatments included a control, NPK fertilizer, AMF biofertilizer, and combinations of AMF biofertilizer with varying doses of NPK fertilizer. Growth parameters were plant height, trunk diameter, frond count, dry matter weight, AMF root infection, and soil spore count. The results showed that the standard dose NPK + 30 g AMF biofertilizer exhibited the best morphological traits, which significantly affected the dry matter weight of seedlings. However, the half standard dose of NPK + 30 g AMF biofertilizer optimized growth while reducing dependence on chemical fertilizers. AMF root infections were observed in the treatments with biofertilizer. These findings indicate that the combined use of NPK fertilizer and AMF can optimize oil palm seedling growth, providing a strong foundation for improved field establishment and future productivity.